Back Cover: Rewiring Translation for Elongation Factor Tu‐Dependent Selenocysteine Incorporation (Angew. Chem. Int. Ed. 5/2013). Issue 5 (20th January 2013) - Aldag, Caroline; Bröcker, Markus J.; Hohn, Michael J.; Prat, Laure; Hammond, Gifty; Plummer, Abigail; Söll, Dieter
<x xml:space="preserve">Abstract</x> Synthetic tRNA for selenoprotein production is described by D. Söll et al. in their Communication on page 1441 ff. The tRNA is a substrate for three E. coli proteins: seryl‐tRNA synthetase (SerRS), selenocysteine synthase (SelA) generating Sec‐tRNAUTu, and EF‐Tu for Sec‐tRNAUTu transport to the ribosome, which allows site‐specific Sec insertion into proteins. This system has general utility in protein engineering, molecular biology, and disease research.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>